Buckybowl polymers: synthesis of corannulene-containing polymers through post-polymerization modification strategy - Barát, Viktor (2022)
In this study, we explore the synthesis of methacrylate polymers carrying buckybowl corannulene as the polymer side-chain. For this, a general reactive scaffold, poly(glycidyl methacrylate) (PGMA), was prepared through an atom transfer radical polymerization process. The glycidyl units of this polymer could be subjected to a nucleophilic ring-opening reaction with mercaptocorannulene. The ring-opening reaction produced a reactive secondary hydroxyl group. These sites could be used to anchor alkyl chains through an esterification reaction. Alternatively, the post-polymerization functionalization could be carried out in one step albeit in a random fashion using two different thiol molecules. Here, the incorporation of an electron-rich thienothiophene moiety is demonstrated along with electron-deficient corannulenes in the polymer chain. The PGMA homopolymer could also be replaced with a random copolymer of methyl methacrylate. In some cases, the ring-opening reaction is carried out only partially to retain the reactive epoxide groups in the molecular structure, which enables further functionalization to alter polymer solubility or allow for intermolecular crosslinking of the structure to obtain thick polymer films. In essence, various simple synthetic strategies to corannulene-encoded and reactive/functionalizable polymers are established in this work.